Financial Advice Markets - Burke, Jeremy; Hung, Angela A. (RAND Corporation, 2023)
This review compares financial advice markets in the United States, the United Kingdom, Australia, Germany, Singapore, and the European Union, where regulatory changes aimed at improving the quality of financial advice have recently been made, to determine how such changes have affected financial advice markets.